2017
DOI: 10.21873/anticanres.11444
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA Ligand PET/CT-based Radiotherapy for Lymph Node Relapse of Prostate Cancer After Primary Therapy Delays Initiation of Systemic Therapy

Abstract: Among patients with prostate cancer, tumor relapse after primary therapy particularly occurs in high-risk groups. The standard of care for distant relapse of prostate cancer is androgen-deprivation therapy (ADT), which has a negative impact on the patient's quality of life (1). Recently alternative local treatment strategies have been proposed for patients with oligometastatic disease, who have a better prognosis than patients with extensive disease (2). Local therapies such as radiotherapy could provide effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The micrometastases were not detected by the PET/CTs. Anyway, an increasing number of studies report that SRT has been guided by 68 Ga-PSMA-HBED-CC PET/CT [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The micrometastases were not detected by the PET/CTs. Anyway, an increasing number of studies report that SRT has been guided by 68 Ga-PSMA-HBED-CC PET/CT [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in patients with locally-recurrent and oligometastatic PCa demonstrated that 68 Ga-PSMA ligand and PET/CT-guided RT is strongly associated with slower clinical progression, thus also delaying initiation of systemic treatment. Moreover, the preliminary results in that cohort suggest that RT with 68 Ga-PSMA ligand PET/CT provides local control, with a substantial treatment response (i.e., lower PSA levels) without clinically-relevant side effects (57). Guler et al retrospectively investigated the efficacy and toxicity of 68 Ga-PSMA PET-CT-guided RT for oligometastatic PCa, finding that this technique may be a promising approach to treatment of patients with biochemically-recurrent PCa (58).…”
Section: Overview Of Pca Imaging Methodsmentioning
confidence: 98%
“…The present study selected patients with PC from prospectively recorded databases of consecutive patients treated with LuPRLT at the six centers. The present study followed conventional eligibility criteria for LuPRLT: informed consent to LuPRLT, age > 18 years, histologically proven PC, hemoglobin > 80 g/l, white blood cell counts > 3 × 10 9 cells/l, platelet counts > 75 × 10 9 cells/l, and alanine aminotransferase, aspartate aminotransferase and, with one exception, creatinine < 1.5 × upper limit of normal values [28, 32].…”
Section: Methodsmentioning
confidence: 99%